A nomogram-based radiomics for predicting survival to concurrent chemoradiotherapy in inoperable pancreatic cancer: a dual-center cohort study - Liu, Xin; Su, Ke; Du, Shanshan; Li, Yanze; Sun, Peiping; Shen, Shucheng; Liang, Benzhe; Chen, Jian; Liu, Rui; Zhang, Rui; Wang, Heran; Wang, Huadong; et al. (Frontiers in Immunology, 2025)
ObjectiveThis study was designed to explore the value of machine learning-based radiology in predicting overall survival (OS) among patients with inoperable pancreatic cancer (PC) who are undergoing concurrent chemoradiotherapy (CCRT).MethodsThis multicenter study enrolled 342 patients with inoperable PC. Firstly, radiomic features were pre-screened by univariate Cox regression and subsequently used to develop 101 machine-learning–based imaging models. An optimized selection algorithm was applied to these models to derive each patient’s radiomic signature (Rad-score). Secondly, key clinical predictors of OS were identified via LASSO–Cox regression and incorporated into clinical nomogram. Finally, the Rad-score was combined with the independent clinical risk factors to construct clinical–radiomics nomogram.ResultsLASSO–Cox regression identified age, clinical stage, tumor size, and albumin level as independent prognostic factors for OS. Based on these four variables, we constructed a clinical nomogram in the training cohort, which achieved a C-index of 0.71. In the internal validation cohort, the areas under the receiver operating characteristic curve (AUC-ROC) for predicting 1-, 2-, and 3-year OS were 0.577, 0.721, and 0.730, respectively; in the external validation cohort, the corresponding AUC-ROCs were 0.841, 0.757, and 0.598. Subsequently, each patient’s Rad-score was integrated with these clinical predictors to develop a clinical–radiomics nomogram, which demonstrated a C-index of 0.892. The AUC-ROCs for predicting 1-, 2-, and 3-year OS were 0.791, 0.846, and 0.840 in the internal validation cohort, and 0.863, 0.830, and 0.734 in the external validation cohort.ConclusionThe clinical–radiomics nomogram demonstrated superior predictive performance for OS compared to the clinical nomogram in inoperable PC patients undergoing CCRT.